The Impact of School Financial Management on Educational Quality: A Qualitative Study at SDN 13 Banyuasin III - Syaphani; Nur Ahyani; Alhadi Yan Putra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to examine the impact of school financial management on educational quality at SDN 13 Banyuasin III. A descriptive qualitative approach was employed involving seven purposively selected informants consisting of one principal, one treasurer, two teachers, one school committee member, and two students. Data were collected through observations, semi-structured interviews, and document analysis. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The findings indicate that effective school financial management, particularly through BOS fund planning, implementation, monitoring, and stakeholder participation, contributed to improving learning facilities, teacher professionalism, learning quality, and public trust. Nevertheless, challenges such as limited BOS funds, delayed fund disbursement, and administrative constraints remained significant obstacles. The study concludes that transparent and accountable financial management is a strategic factor in improving educational quality.